Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the given matrix operations, we need to perform addition, subtraction, scalar multiplication, and a combination of these on the matrices provided. Here are the matrices:
[tex]\[ A = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right], \quad B = \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] \][/tex]
### (a) [tex]\(A + B\)[/tex]
To find [tex]\(A + B\)[/tex], we add the corresponding elements of matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A + B = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] + \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{cc} 3 + (-2) & 1 + (-2) \\ 1 + 1 & 3 + 2 \end{array}\right] = \left[\begin{array}{cc} 1 & -1 \\ 2 & 5 \end{array}\right] \][/tex]
So, [tex]\(A + B = \left[\begin{array}{cc} 1 & -1 \\ 2 & 5 \end{array}\right]\)[/tex].
### (b) [tex]\(A - B\)[/tex]
To find [tex]\(A - B\)[/tex], we subtract the corresponding elements of matrix [tex]\(B\)[/tex] from matrix [tex]\(A\)[/tex]:
[tex]\[ A - B = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] - \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{cc} 3 - (-2) & 1 - (-2) \\ 1 - 1 & 3 - 2 \end{array}\right] = \left[\begin{array}{cc} 5 & 3 \\ 0 & 1 \end{array}\right] \][/tex]
So, [tex]\(A - B = \left[\begin{array}{cc} 5 & 3 \\ 0 & 1 \end{array}\right]\)[/tex].
### (c) [tex]\(5A\)[/tex]
To find [tex]\(5A\)[/tex], we multiply each element of matrix [tex]\(A\)[/tex] by the scalar [tex]\(5\)[/tex]:
[tex]\[ 5A = 5 \cdot \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] = \left[\begin{array}{cc} 5 \cdot 3 & 5 \cdot 1 \\ 5 \cdot 1 & 5 \cdot 3 \end{array}\right] = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right] \][/tex]
So, [tex]\(5A = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right]\)[/tex].
### (d) [tex]\(5A - 2B\)[/tex]
To find [tex]\(5A - 2B\)[/tex], we first find [tex]\(2B\)[/tex] by multiplying each element of matrix [tex]\(B\)[/tex] by the scalar [tex]\(2\)[/tex], and then subtract it from [tex]\(5A\)[/tex].
[tex]\[ 2B = 2 \cdot \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{rr} 2 \cdot (-2) & 2 \cdot (-2) \\ 2 \cdot 1 & 2 \cdot 2 \end{array}\right] = \left[\begin{array}{rr} -4 & -4 \\ 2 & 4 \end{array}\right] \][/tex]
Now, subtract [tex]\(2B\)[/tex] from [tex]\(5A\)[/tex]:
[tex]\[ 5A - 2B = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right] - \left[\begin{array}{rr} -4 & -4 \\ 2 & 4 \end{array}\right] = \left[\begin{array}{cc} 15 - (-4) & 5 - (-4) \\ 5 - 2 & 15 - 4 \end{array}\right] = \left[\begin{array}{cc} 19 & 9 \\ 3 & 11 \end{array}\right] \][/tex]
So, [tex]\(5A - 2B = \left[\begin{array}{cc} 19 & 9 \\ 3 & 11 \end{array}\right]\)[/tex].
[tex]\[ A = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right], \quad B = \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] \][/tex]
### (a) [tex]\(A + B\)[/tex]
To find [tex]\(A + B\)[/tex], we add the corresponding elements of matrices [tex]\(A\)[/tex] and [tex]\(B\)[/tex]:
[tex]\[ A + B = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] + \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{cc} 3 + (-2) & 1 + (-2) \\ 1 + 1 & 3 + 2 \end{array}\right] = \left[\begin{array}{cc} 1 & -1 \\ 2 & 5 \end{array}\right] \][/tex]
So, [tex]\(A + B = \left[\begin{array}{cc} 1 & -1 \\ 2 & 5 \end{array}\right]\)[/tex].
### (b) [tex]\(A - B\)[/tex]
To find [tex]\(A - B\)[/tex], we subtract the corresponding elements of matrix [tex]\(B\)[/tex] from matrix [tex]\(A\)[/tex]:
[tex]\[ A - B = \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] - \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{cc} 3 - (-2) & 1 - (-2) \\ 1 - 1 & 3 - 2 \end{array}\right] = \left[\begin{array}{cc} 5 & 3 \\ 0 & 1 \end{array}\right] \][/tex]
So, [tex]\(A - B = \left[\begin{array}{cc} 5 & 3 \\ 0 & 1 \end{array}\right]\)[/tex].
### (c) [tex]\(5A\)[/tex]
To find [tex]\(5A\)[/tex], we multiply each element of matrix [tex]\(A\)[/tex] by the scalar [tex]\(5\)[/tex]:
[tex]\[ 5A = 5 \cdot \left[\begin{array}{cc} 3 & 1 \\ 1 & 3 \end{array}\right] = \left[\begin{array}{cc} 5 \cdot 3 & 5 \cdot 1 \\ 5 \cdot 1 & 5 \cdot 3 \end{array}\right] = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right] \][/tex]
So, [tex]\(5A = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right]\)[/tex].
### (d) [tex]\(5A - 2B\)[/tex]
To find [tex]\(5A - 2B\)[/tex], we first find [tex]\(2B\)[/tex] by multiplying each element of matrix [tex]\(B\)[/tex] by the scalar [tex]\(2\)[/tex], and then subtract it from [tex]\(5A\)[/tex].
[tex]\[ 2B = 2 \cdot \left[\begin{array}{rr} -2 & -2 \\ 1 & 2 \end{array}\right] = \left[\begin{array}{rr} 2 \cdot (-2) & 2 \cdot (-2) \\ 2 \cdot 1 & 2 \cdot 2 \end{array}\right] = \left[\begin{array}{rr} -4 & -4 \\ 2 & 4 \end{array}\right] \][/tex]
Now, subtract [tex]\(2B\)[/tex] from [tex]\(5A\)[/tex]:
[tex]\[ 5A - 2B = \left[\begin{array}{cc} 15 & 5 \\ 5 & 15 \end{array}\right] - \left[\begin{array}{rr} -4 & -4 \\ 2 & 4 \end{array}\right] = \left[\begin{array}{cc} 15 - (-4) & 5 - (-4) \\ 5 - 2 & 15 - 4 \end{array}\right] = \left[\begin{array}{cc} 19 & 9 \\ 3 & 11 \end{array}\right] \][/tex]
So, [tex]\(5A - 2B = \left[\begin{array}{cc} 19 & 9 \\ 3 & 11 \end{array}\right]\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.